Revitalisasi Kolong Flyover Cileungsi Sebagai Program Penataan Infrastruktur - Firdaus, Aliefia Azalia; Toyib, Muhammad Ibnu; Syaratunnisa, Syaratunnisa; Utarindasari, Destiana (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2024)
ABSTRACT The revitalization underneath of the Cileungsi Flyover is one of the infrastructure arrangement programs that transforms the slum and unmaintained area underneath the Cileungsi Flyover into a comfortable and beneficial area for the community, for example by creating a mini park. The Community Service Program aims to optimize the use of public spaces, improve environmental quality, support sustainable infrastructure development and educate the public about the importance of maintaining environmental cleanliness. The background of this problem is the rampant people who throw garbage into the Cileungsi Flyover area and the condition of the infrastructure underneath the Cileungsi Flyover which is shabby and unmaintained. With the purpose of the Program Kuliah Kerja Nyata (KKN) for students, it is hoped that it can be a new learning experience to increase knowledge, abilities, and awareness of community life. The results of this activity show an increase in public awareness about the importance of maintaining environmental cleanliness, Cleanliness and aesthetics of the Cileungsi Flyover underneath area. In addition to having a physical impact, this program also forms a family relationship between students, youth organizations of Cileungsi Kidul Village and Cileungsi District through the Forum Masyarakat Peduli Cileungsi(FMPC) is very important for the success of the program. It is hoped that the success of this program will be an inspiring example for the next KKN activities and continue to make a positive contribution to the community and the environment. Keywords: Revitalization,Flyover, infrastructure arrangement